Bioabsorbable steroid‐releasing implants in the frontal sinus ostia: a pooled analysis - Singh, Ameet (Int Forum Allergy Rhinol, 2018)
BACKGROUND: Bioabsorbable steroid‐releasing implants (mometasone furoate, 370 μg) are effective for improving postsurgical outcomes in the frontal sinus ostia (FSO). In this study we evaluated the effect of these implants on frontal outcomes in various patient subgroups with chronic rhinosinusitis (CRS) using pooled data from 2 randomized, controlled trials (RCTs). METHODS: A total of 160 subjects were enrolled in 2 RCTs. After surgery, subjects were randomized to receive an implant in 1 FSO with the contralateral side as control. Data through day 90 from the 2 studies were pooled and subgroup analyses were performed. RESULTS: At day 30, relative to controls, steroid‐releasing implants significantly reduced the need for postoperative interventions by 46.8% (95% confidence interval [CI], −60.7 to −27.9), for surgical interventions by 51.2% (95% CI, −68.2 to −25.2), and for oral steroid interventions by 37.2% (95% CI, −54.6 to −13.1) in the pooled data set. At day 90, statistically significant reductions (p < 0.05) in the need for postoperative interventions (relative reduction [RR], 30.2%), restenosis/occlusion rate (RR, 31.7%), and inflammation score (absolute difference, −6.0), and increase in estimated FSO diameter (absolute difference, 1 mm), favoring the treated side, were observed. Subgroup analyses of the pooled data showed statistically significant improvements (p < 0.05) at day 90 in restenosis/occlusion rate, and estimated FSO diameter, favoring the treated side across subgroups, with no statistically significant subgroup‐by‐treatment interactions. CONCLUSION: Bioabsorbable steroid‐releasing sinus implants improve outcomes of frontal sinus surgery through 90 days, irrespective of asthma status, previous endoscopic sinus surgery, extent of surgery, extent of polyps, or Lund‐Mackay computed tomography stage in the FSO.